Glycosphingolipid depletion in PC12 cells using iminosugars protects neuronal membranes from anti-ganglioside antibody mediated injury. - Townson, K; Speak, A; Greenshields, K; Goodyear, C; Willison, H; Platt, F (2008)
Autoimmune neuropathies are frequently associated with pathogenic anti-ganglioside antibodies targeting ganglioside-rich neuronal and glial membranes. The extent of injury is determined by the concentration of membrane ganglioside and thus reduction might be expected to attenuate disease. In this study, we suppressed ganglioside biosynthesis in PC12 cells with the glucosylceramide synthase inhibitor, N-butyldeoxynojirimycin and observed reduced plasma membrane antibody binding and a major neuroprotective effect in complement-mediated lysis assays. These data demonstrate that iminosugar inhibitors, currently used to treat type 1 Gaucher disease, are also of potential value for depleting antigen and thereby suppressing tissue injury in anti-ganglioside antibody-associated neuropathy.